A novel variant in MYBPC3 causes hypertrophic cardiomyopathy by haploinsufficiency - Yuanyuan Zhang; Wenyan Gong; Yusheng Cong; Xingwei Zhang; Zhelan Zheng (PLoS ONE, 2025)
Background Familial hypertrophic cardiomyopathy (HCM) is the most common genetic cardiovascular disease (CVD). Related mutations contributing to hypercontractility and poor relaxation in HCM are not completely understood. Purpose This study aimed to explore and verify a novel variant of cardiac myosin-binding protein C (cMyBP-C, encoded by MYBPC3 ) in an HCM family. Methods Clinical information and cardiac parameters were collected in the pedigree. Genomic DNA was extracted from peripheral blood and second-generation sequencing technology was used to investigate the proband and his family members. Subsequent sequence analysis was performed with DNAMAN software. The cardiac expression levels of MYBPC3 mRNA and cMyBP-C protein were assessed using RT-qPCR and Western blot analysis, respectively. Results Typical interventricular septal thickening was detected in all four HCM patients without left ventricular outflow tract obstruction. The c.1042_1043insCGGCA mutation in MYBPC3 was verified in the proband and family members. In silico analysis of the mutation revealed that c.1042_1043insCGGCA led to a shift in the sequence of nucleotides, creating a premature stop codon at the new reading frame. RT-qPCR analysis of MYBPC3 mRNA revealed a marked reduction in HCM heart compared to the normal controls (P < 0.05). Consistently, Western blot analysis showed significantly reduced expression of cMyBP-C in the pedigree in comparison with the controls (P < 0.05). Conclusion The novel c.1042_1043insCGGCA MYBPC3 mutation is a genetic basis for HCM due to c-MyBP-C haploinsufficiency.